Diet's Cariogenicity and Healthfulness Index (DCHI) - A Novel, Comprehensive Index for Children - Raghavendra Shanbhog; H. P. Chanchala; K. T. Srilatha; B. Madhu; S.N. Manjunatha (Wolters Kluwer Medknow Publications, 2024)
Background: Realistic and tailored dietary advice plays a vital role in Preventive Dentistry. An appropriate diet analysis forms the basis for precise dietary advice. Analysis of diet for its cariogenicity is a complex process. Performing a meaningful diet analysis is a challenge in routine clinical practice. Currently, very few tools are available for clinicians to assess children's diet relating to caries risk. The current scientific paper presents a novel index that assesses the cariogenicity and healthfulness of a child's diet objectively and guides the professional to achieve pragmatic diet modification in the prevention of dental caries. Methods: Multi-disciplinary teams with a sample study population were involved in the initial structuring of Diet's Cariogenicity and Healthfulness Index. To obtain cut-off values for cariogenicity of diet, a study was carried out with a sample of 774 children correlating diet diary with caries status. For statistics, the Receiver Operating Characteristic (ROC) curve closest to the ideal of 100% sensitivity and 100% specificity was applied. Results: ROC curve of 22.5 were plotted for diet scores for its cariogenicity. The sensitivity, specificity, and area under the curve of these cut-off values were 70 and 95, respectively. Conclusions: The current scientific paper presents a novel Diet's Cariogenicity and Healthfulness Index that assesses the cariogenicity and healthfulness of a child's diet objectively to guide the professional to achieve a logical diet modification.